THE EFFECT OF PRACTICAL SPSS TRAINING ON STUDENTS’ RESEARCH COMPETENCE; A SURVEY OF JOMO KENYATTA UNIVERSITY OF AGRICULTURE AND TECHNOLOGY MOMBASA CAMPUS POSTGRADUATE STUDENTS - Kimani, John Githii; Simba, Dr Fridah (African Journal of Education and Practice, 2017)
Purpose: The purpose of the paper is to assess the effectiveness of the practical SPSS training to students' research competency. Methodology: An explanatory research design was used to establish the relationship between practical SPSS training and research competence of students. The population was 38 students and a census of the full population was taken. A questionnaire was administered at the end of the training to capture the pre and post training experience and test the effectiveness of the training. The analysis of the data was conducted through descriptive and inferential statistics. In particular, frequencies, means, standard deviations and paired t-test were used. Results: The post training evaluation results reveal that majority of the respondents had low knowledge in data entry, descriptive statistics, regression and correlation analysis, parametric and non-parametric analysis, and journal article extraction and publication. Results also reveal that the level of knowledge significantly increased after the training. This is supported by the paired t-tests conducted on each aspect of training. Unique Contribution to Theory, Policy and Practice: It was recommended to the campus director that frequent trainings be organized at the convenience of the campus. It was suggested that DVC academic affairs can consider supporting the training financially or the students to be requested to pay a token fee to make the training sustainable. It was suggested that the training can be made compulsory for all students undertaking Business Research Methods and points to accrue once they attend the training. The results were useful in theory building as they validated the efficacy of practical training pedagogical approaches. Key words: SPSS, Practical Training, Research Competence, Post Graduate Students